Unsteady double-diffusive natural convection in a two-sided lid-driven inclined porous enclosure with sinusoidal boundary conditions with Soret and Dufour effects. (4th May 2019) - Mondal, S.; Sibanda, P.; Mandal, P.K.; Murthy, P.V.S.N.
ABSTRACT: Unsteady double-diffusive natural convection in an inclined porous enclosure with sinusoidal boundary conditions and Soret and Dufour parameters is studied. The unique aspects of the set-up are that the left vertical and bottom walls are heated and concentrated non-uniformly and uniformly, respectively, while the right vertical wall is well insulated and the top wall is maintained at a constant concentration and cold temperature. A staggered grid finite-difference method is used to solve the system of partial differential equations that model heat and mass transfer inside the enclosure. We demonstrate the effects of the Soret and Dufour parameters and the inclination angle on the unsteady double-diffusive natural convection in the inclined porous enclosure. With all the numerical studies, the least square curve fitting (exponential non-linear curve fitting) of average Nusselt number and average Sherwood number with respect to different Soret and Dufour numbers at the left vertical wall which is non-uniformly heated and concentrated is examined here. Comparison with previously published results shows an excellent agreement.